Penerapan Seni Tepat Guna Dalam Pengolahan Informasi Visual Untuk Lihai Islamic Preschool Bandung - Wahab, Taufiq; Hidayat, Syarip; Suprayogi, Bambang Melga; Shahira, Rafa (LPPM UNIVERSITAS DIAN NUSWANTORO, 2025)
Early Childhood Education shapes children's intellectual development, character, and Islamic values. Lihai Islamic Preschool in Bandung became a community service partner to design a visual information design solution with an Islamic approach. This program aims to utilize empty school areas as interesting and educational visual information media, including depictions of animal characters from the Koran in children's daily activities. The design process involves needs analysis, concept discussion with the school, and design implementation. This visual information is expected to not only beautify the school environment but also support learning through creative visual media. This program demonstrates that successful graphic design is not only aesthetically pleasing, but also has a positive social and educational impact. The implementation results provide a more attractive environment for children as well as an effective learning medium. In the future, this solution can be developed into other forms of information media that are more flexible and dynamic as needed.